2014
DOI: 10.1007/s00442-014-3054-z
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass response to CO2 contingent on epiphytic algae: indirect effects can overwhelm direct effects

Abstract: Increased availability of dissolved CO2 in the ocean can enhance the productivity and growth of marine plants such as seagrasses and algae, but realised benefits may be contingent on additional conditions (e.g. light) that modify biotic interactions between these plant groups. The combined effects of future CO2 and differing light on the growth of seagrass and their algal epiphytes were tested by maintaining juvenile seagrasses Amphibolis antarctica under three different CO2 concentrations representing ambient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 73 publications
2
34
2
Order By: Relevance
“…This might seem obvious, but the DBL-induced impedance of O 2 exchange with the water-column of plants with epiphyte-cover, could also have resulted in an enhancement in the aerenchymal O 2 level (seen as the build-up in the surface O 2 concentration on Figure 5) and thereby a concomitant higher ROL from the root-apex, but this effect was apparently overruled by lower seagrass photosynthesis due to epiphyte shading and/or inorganic carbon limitation due to increased DBL thickness. Burnell et al (2014) recently demonstrated that high incident photon irradiance (∼200 µmol photons m −2 s −1 ) in combination with elevated water-column CO 2 concentrations (up to 900 µl L −1 , representing future predictions of enhanced water-column CO 2 levels) had a negative effect on seagrass biomass and leaf growth, as compared to low light conditions. The observed negative growth response to combined high CO 2 and light conditions appeared to be closely related to overgrowth of seagrass leaves with filamentous algal epiphytes.…”
Section: Dark O 2 Microdynamics In the Rhizospherementioning
confidence: 99%
“…This might seem obvious, but the DBL-induced impedance of O 2 exchange with the water-column of plants with epiphyte-cover, could also have resulted in an enhancement in the aerenchymal O 2 level (seen as the build-up in the surface O 2 concentration on Figure 5) and thereby a concomitant higher ROL from the root-apex, but this effect was apparently overruled by lower seagrass photosynthesis due to epiphyte shading and/or inorganic carbon limitation due to increased DBL thickness. Burnell et al (2014) recently demonstrated that high incident photon irradiance (∼200 µmol photons m −2 s −1 ) in combination with elevated water-column CO 2 concentrations (up to 900 µl L −1 , representing future predictions of enhanced water-column CO 2 levels) had a negative effect on seagrass biomass and leaf growth, as compared to low light conditions. The observed negative growth response to combined high CO 2 and light conditions appeared to be closely related to overgrowth of seagrass leaves with filamentous algal epiphytes.…”
Section: Dark O 2 Microdynamics In the Rhizospherementioning
confidence: 99%
“…) and was observed between epiphytes and the seagrass Amphibolis antartica under high‐light and elevated CO 2 (Burnell et al . ). Among epiphytic groups, coralline algae and foraminifera are calcifying along with several species of polychaetes that form calcified tubes and some bryozoans that have calcified surfaces.…”
Section: Introductionmentioning
confidence: 97%
“…; Burnell et al . ) and reproduction (Palacios & Zimmerman ). However, benefits for seagrasses may largely depend on biological interactions that are difficult to mimic in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to seedlings, as P. oceanica seedlings grown under elevated CO 2 improved photosynthetic performance, and developed larger carbon storage in belowground tissues, having thus more resources to tolerate and recover from stressors. However, elevated CO 2 also favors filamentous algae, which can overgrow seagrass seedlings, leading to reduced growth (Burnell et al, 2014). Moreover, lower N content and increased sucrose levels in seedlings growing under high pCO 2 lead to higher herbivory pressure (Hernán et al, 2016).…”
Section: B2 Propagation Success: Climate Change Impacts On Early Lifementioning
confidence: 99%